Simulação em terminais de cargas: um estudo do transporte de carga aérea no Aeroporto Internacional do Rio de Janeiro - Cascardo, Leonardo Macedo Rodrigues (2017)
The aim of this study is to analyse a cargo transport process in an air cargo warehouse, using concepts of process improvement in order to evaluate possible solutions to problems identified. This is done by analysing the processes of a cargo warehouse to create a simulation model and to test corrective measures in different scenarios. The methodologies used in this dissertation were bibliographic research and case study including interviews. Rio de Janeiro International Airport import cargo warehouse was the place chosen for the case study. This work supports the importance to study proposed solutions through the use of simulation in order to justify to attract investments in the area. A simulation model is created during this study. The objective is to simulate the operation of Rio de Janeiro International Airport import cargo warehouse. The simulation runs from the moment of parking of an aircraft until the final delivery of cargo to the final client. Many stages are simulated, such as the storage process. After validating the model, different scenarios are created to simulate different situations such as the operation in 2024 with an increase of demand and the test of system improvements with the increase in the number of work stations along the process and the construction of a new access road from the passenger terminal to the cargo warehouse. The results showed bottlenecks in the system in the future which were resolved by the implementation of improvements.